2013
DOI: 10.1002/wrcr.20452
|View full text |Cite
|
Sign up to set email alerts
|

Beyond peak reservoir storage? A global estimate of declining water storage capacity in large reservoirs

Abstract: [1] Water storage is an important way to cope with temporal variation in water supply and demand. The storage capacity and the lifetime of water storage reservoirs can be significantly reduced by the inflow of sediments. A global, spatially explicit assessment of reservoir storage loss in conjunction with vulnerability to storage loss has not been done. We estimated the loss in reservoir capacity for a global data set of large reservoirs from 1901 to 2010, using modeled sediment flux data. We use spatially exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
83
0
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 165 publications
(86 citation statements)
references
References 37 publications
1
83
0
2
Order By: Relevance
“…Lettenmaier and Milly (2009) indicated that the volume of silt accumulated in reservoirs should be removed, which is equal to *4 mm sea level equivalent. Indeed, silting-up of existing reservoirs may already be, or in coming decades may become, a larger effect on impoundment than the construction of new reservoir capacity (Wisser et al 2013). It is also important to note that climate-driven land water storage change has a large negative contribution to SLR over the period 2002-2014.…”
Section: Updated Land Water Contribution and Discussionmentioning
confidence: 99%
“…Lettenmaier and Milly (2009) indicated that the volume of silt accumulated in reservoirs should be removed, which is equal to *4 mm sea level equivalent. Indeed, silting-up of existing reservoirs may already be, or in coming decades may become, a larger effect on impoundment than the construction of new reservoir capacity (Wisser et al 2013). It is also important to note that climate-driven land water storage change has a large negative contribution to SLR over the period 2002-2014.…”
Section: Updated Land Water Contribution and Discussionmentioning
confidence: 99%
“…Lots of papers are published regarding the reservoir sedimentation, monitoring, and balancing (Amitrano et al, 2013;Ali et al, 2014), ecology and sustainability (Detering and Schuettrumpf, 2014) comparative analysis and assessment (Hajji et al, 2014;Bennett et al, 2013;Garg & Jothiprakash, 2013;Wisser et al, 2013;Andredaki, et al, 2014;Gopinath et al, 2014), methodology and management (Hosseinjanzadeh et al, 2015;Dewals et al, 2012), reservoirs modeling and silting prism dynamic (Caputo and Carcione, 2013;Mattheus, 2013;Mansikkamäki, 2013), avoiding the effect on the environment and the catastrophic water floods (Ran et al, 2013;Matchavariani et al, 2016), research on the experiment of reservoir water treatment (Zhang et al, 2016), etc.…”
Section: Methodsmentioning
confidence: 99%
“…Among all of these, water supply is a most important operation and highly depends on the reservoir storage capacity. According to the statistics, the capacity of large reservoirs in the world had decreased 5% from 1901 to 2010 [1]. As the world's population increases, reservoir sedimentation will pose more challenges in the utilization of water resources.…”
Section: Introductionmentioning
confidence: 99%